2006
DOI: 10.1038/sj.eye.6702345
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and visual acuity following transscleral diode laser photocoagulation in cases of refractory and non-refractory glaucoma

Abstract: Aims Transscleral diode laser cyclophotocoagulation (TSCP) is widely accepted in the treatment of refractory glaucoma especially in eyes with poor vision. However, until recently, there has been a reluctance to extend its use to eyes with good visual acuity (VA). The aims of this study were to evaluate the long-term efficacy and safety of TSCP for a range of glaucoma conditions, with particular emphasis on post-treatment VA in seeing eyes. Methods A retrospective analysis of case notes of 74 treated eyes was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 17 publications
4
72
1
3
Order By: Relevance
“…[34][35][36][37][38][39] This may be related to the lower energy settings and the relatively higher proportion of primary open-angle glaucoma and less severe forms of glaucoma than in prior studies.…”
Section: Complicationsmentioning
confidence: 58%
See 3 more Smart Citations
“…[34][35][36][37][38][39] This may be related to the lower energy settings and the relatively higher proportion of primary open-angle glaucoma and less severe forms of glaucoma than in prior studies.…”
Section: Complicationsmentioning
confidence: 58%
“…38 Egbert et al 34 used diode TCP soon after the institution of antihypertensive drops in recently diagnosed cases of glaucoma in Ghana. Because of the relative poor access to healthcare and medical treatment, TCP was evaluated as a plausible and relatively noninvasive alternative.…”
Section: Indications For Ecp and Tcpmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of topical drugs required for IOP control also reduced significantly in all subgroups of patients. Other studies have also demonstrated 100% freedom from oral acetazolamide following DLCP, 15,30 whereas in the study by Spencer and Vernon 24 (who used a lower energy treatment protocol), 91% of patients were free from oral acetazolamide.…”
Section: Transcleral Diode Laser Cyclophotocoagulation S Kaushik Et Almentioning
confidence: 96%